2012
DOI: 10.1037/a0025522
|View full text |Cite
|
Sign up to set email alerts
|

The role of masculine norms and informal support on mental health in incarcerated men.

Abstract: Mental health problems, in general, and major depression in particular, are prevalent among incarcerated men. It is estimated that 23% of state inmates report experiencing symptoms of major depression. Despite the high rates of depressive symptoms, there is little understanding about the psychosocial factors that are associated with depressive and anxiety symptoms of incarcerated men. One factor relevant to the mental health of incarcerated men is their adherence to traditional masculine norms. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 36 publications
0
48
0
2
Order By: Relevance
“…Moderation analyses confirmed that the difference was statistically significant. To the extent that men in these populations are denied status or expectation of status within a culture of traditional masculinity in the United States (Bowleg et al, 2011; Gordon, et al, 2013; Iwamoto et al, 2011; Iwamoto et al, 2012; Murphy et al, 2013; Wade & Rochlen, 2013), both partners may have felt that it was important to maintain a semblance of status for male partners, as indicated in a prior qualitative study (Bowleg et al, 2004). This could have led to deference to men, thus reducing women’s sense of agency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moderation analyses confirmed that the difference was statistically significant. To the extent that men in these populations are denied status or expectation of status within a culture of traditional masculinity in the United States (Bowleg et al, 2011; Gordon, et al, 2013; Iwamoto et al, 2011; Iwamoto et al, 2012; Murphy et al, 2013; Wade & Rochlen, 2013), both partners may have felt that it was important to maintain a semblance of status for male partners, as indicated in a prior qualitative study (Bowleg et al, 2004). This could have led to deference to men, thus reducing women’s sense of agency.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional masculinity may exclude certain groups of individuals (e.g., Blacks, women, homosexuals) while privileging White men (Connell & Messerschmidt, 2005; Wade, 2008), anyone is subject to it regardless of their social status (Iwamoto, Cheng, Lee, Takamatsu, & Gordon, 2011; Iwamoto et al, 2012). This is important for some men of color, who, because of their social status, may be unable to “fully” attain ideals of traditional masculinity, yet are still subject to it.…”
Section: Race-ethnicity and Gender As Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The masculine role adopted by many men fosters gendered lifestyles and behaviour. 12,13 Men are taught to be independent, fearless, and strong. As such, they avoid seeking help or acknow ledging weakness or vulnerability, which can adversely affect their health.…”
Section: What Comprises Men's Health?mentioning
confidence: 99%
“…Social support, a cognitive process whereby one is loved, esteemed, and a part of a network of spouses, friends and family members who provide psychological and material resources (Cohen & Wills, 1985) has been consistently linked to better mental health (Iwamoto et al, 2012). Existing literature (Hays, Turner, & Coates, 1992; Iwamoto et al, 2012) has documented that the experience of social support moderates the effects of HIV symptom expression and masculinity on depression and stress (Broadhead et al, 1983; House, Landis, & Umberson, 1988). There have been calls for research that examines how the contextual issues impacting individuals affect their use and experience of social support (Braveman, Egerter, & Williams, 2011; Thoits, 1995).…”
Section: Introductionmentioning
confidence: 99%